Evaluating Adaptive Reuse Criteria for Malaysia’s Pre-war Shophouses: A Correlation Analysis - Ebas, Nur Ain; MOHD ABDULLAH, MUHAMMAD SHAHRIL; Muhamad Jamil, Siti Afiqah; Suratkon, Azeanita (International Journal of Sustainable Construction Engineering and Technology, 2024)
Pre-war shophouses are among the historic structures that deserve preservation, including adaptive reuse. The preservation of old and historic buildings is thought to be possible through the implementation of adaptive reuse. However, choosing between adaptive reuse and other options is difficult because of the need to consider many factors. Therefore, the adaptive reuse criteria must be taken into account before selecting a potential adaptive reuse. There are six broad parameters of adaptive reuse criteria: Economy, Social, Legislative, Technology, Architecture, and Environment. A pilot survey was conducted on heritage experts such as the local authorities (town planners) in each state, architects’ firms, and the Valuation and Property Service Department (JPPH). Thirty-three criteria were found in a heritage building in Malaysia. SPSS is used to analyze these criteria to determine the significance level of each criterion in Malaysia’s heritage buildings. It helps and assists the key parties in making decisions to reuse the prewar shophouse rather than demolishing and replacing it with new structures. This conversion of existing building structures is environmentally sustainable because it entails reusing resources while also retaining the morphological structure of urban areas. Additionally, the results show that all the variables (criteria) have a strong correlation among each other.